2016
DOI: 10.1007/s10620-016-4160-z
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hepatitis B Is Associated with Higher Inpatient Resource Utilization and Mortality Versus Chronic Hepatitis C

Abstract: Despite higher per case resource utilization following hospitalization, HBV-infected patients demonstrate a lower inpatient survival in comparison with chronic HCV infection. These disparate observations underscore the need for early diagnosis of chronic HBV infection in at-risk population and prompt linkage to care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Recent studies in the US, conducted using the Nationwide Inpatient Sample (NIS), found that HBV-infected patients incurred higher inpatient resource utilization and greater inpatient mortality when compared to patients hospitalized with chronic HCV infection or alcoholic liver disease. [ 6 , 7 ] However, due to the cross sectional nature of the data, event-level records not patient-level recordings, these prior studies could not capture if patients required additional hospitalizations or patients died somewhere else than in a hospital. Furthermore, these studies are limited in that they reflect only liver-related utilization and deaths and represent national trends, which may not be applied to some states where high-risk populations are prevalent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in the US, conducted using the Nationwide Inpatient Sample (NIS), found that HBV-infected patients incurred higher inpatient resource utilization and greater inpatient mortality when compared to patients hospitalized with chronic HCV infection or alcoholic liver disease. [ 6 , 7 ] However, due to the cross sectional nature of the data, event-level records not patient-level recordings, these prior studies could not capture if patients required additional hospitalizations or patients died somewhere else than in a hospital. Furthermore, these studies are limited in that they reflect only liver-related utilization and deaths and represent national trends, which may not be applied to some states where high-risk populations are prevalent (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…7 Importantly, the population previously diagnosed with CHB has continued to age, and if untreated, may progress to more advanced liver disease with higher healthcare resource demands. 8,9 Currently, there are limited data on the healthcare utilization and costs associated with CHB in the US. Therefore, the aim of this study was to estimate the annual healthcare resource utilization and costs of liver disease associated with CHB in a large diverse population of patients with CHB in the US, with three types of insurance coverage, compared to matched non-CHB controls.…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, chronic hepatitis B (CHB) resulted in 884,000 deaths, mostly from complications of cirrhosis and hepatocellular carcinoma (HCC) . In the United States, recent population‐based data showed that the economic burden for hospital care of CHB patients is considerable and higher in patients with CHB compared to those with chronic hepatitis C …”
mentioning
confidence: 99%
“…H epatitis B virus (HBV) affects an estimated 257 million people worldwide. (1) In 2015, chronic hepatitis B (CHB) resulted in 884,000 deaths, mostly from complications of cirrhosis and hepatocellular carcinoma (HCC).(1) In the United States, recent population-based data showed that the economic burden for hospital care of CHB patients is considerable and higher in patients with CHB compared to those with chronic hepatitis C. (2,3) Currently, there are effective and well-tolerated oral anti-HBV drugs for long-term or lifelong suppressive treatment with little or no risk of antiviral resistance.…”
mentioning
confidence: 99%